2001
DOI: 10.1007/s00248-001-0004-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of Metabolic Inhibitors to Characterize Ecological Interactions in an Estuarine Microbial Food Web

Abstract: A B S T R A C TUnderstanding microbial food web dynamics is complicated by the multitude of competitive or interdependent trophic interactions involved in material and energy flow. Metabolic inhibitors can be used to gain information on the relative importance of trophic pathways by uncoupling selected microbial components and examining the net effect on ecosystem structure and function. A eukaryotic growth inhibitor (cycloheximide), a prokaryotic growth inhibitor (antibiotic mixture), and an inhibitor of phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Vibriosis and photobacteriose are the two most common types of bacterial diseases that can afflict marine, estuarine and sometimes freshwater farming systems and are principally responsible for the greatest impacts already reported in aquaculture (Defoirdt et al, 2007). In addition to the damage posed by the presence of bacterioplankton and mycoplankton in cultures, these microorganisms also interfere in aquatic scientific experiments, generating methodological problems that will be reflected on results (Spencer, 1952;Yetka & Wiebe, 1974), or making it impossible to test hypothesis about the role of bacteria and fungi in an ecosystem or community (DeLorenzo et al, 2001;Trottet et al, 2011).…”
Section: Effects Of Bacteria and Fungi In Culturesmentioning
confidence: 99%
“…Vibriosis and photobacteriose are the two most common types of bacterial diseases that can afflict marine, estuarine and sometimes freshwater farming systems and are principally responsible for the greatest impacts already reported in aquaculture (Defoirdt et al, 2007). In addition to the damage posed by the presence of bacterioplankton and mycoplankton in cultures, these microorganisms also interfere in aquatic scientific experiments, generating methodological problems that will be reflected on results (Spencer, 1952;Yetka & Wiebe, 1974), or making it impossible to test hypothesis about the role of bacteria and fungi in an ecosystem or community (DeLorenzo et al, 2001;Trottet et al, 2011).…”
Section: Effects Of Bacteria and Fungi In Culturesmentioning
confidence: 99%
“…Some authors who found assumptions to be violated nonetheless concluded that eukaryotic inhibitors are useful for revealing qualitative information about microbial food-web dynamics in natural communities (e.g. Sherr et al 1986;DeLorenzo et al 2001). We disagree with this conclusion.…”
Section: Comments and Recommendationsmentioning
confidence: 99%
“…3c). Antibiotics such as penicillin, streptomycin and neomycin have been applied in cultures to inhibit bacterial contamination without negative effects in microalgae (Molina-Cárdenas et al 2016), protozoans (Divan and Schnoes 1982), fish (Forberg et al 2011), mollusks (Howes et al 2014), crustaceans (Agostini et al 2016) and ecological assays with the aquatic community (Middelburg and Nieuwenhuize 2000a, b;DeLorenzo et al 2001;Veuger et al 2004;Cozzi and Cantoni 2006;Trottet et al 2011). The concentration of these antibiotics, however, needs to be evaluated before application in cultures.…”
Section: Resultsmentioning
confidence: 99%
“…This study consisted of experiments to evaluate the effects of different antibiotics (penicillin, streptomycin and neomycin) at different concentrations (Agostini et al 2016;DeLorenzo et al 2001) administered in combination with nystatin (Finley 2012) (Table 1) to plankton cultures. The experimental organisms evaluated were Acartia tonsa Dana 1849 (Copepoda: Calanoida), Amphibalanus improvisus (Darwin 1854) (Crustacea: Cirripedia), and Conticribra weissflogii (Grunow) Stachura-Suchoples & Williams (Ochrophyta: Bacillariophyceae).…”
Section: Methodsmentioning
confidence: 99%